The Conversion of a Practice-Based Lifestyle Enhancement Program into a Formalized, Testable Program: From Texercise Classic to Texercise Select - Ory, Marcia G.; Smith, Matthew Lee; Howell, Doris; Zollinger, Alyson; Quinn, Cindy; Swierc, Suzanne M.; Stevens, Alan B. (Frontiers in Public Health, 2015)
*